Acute Tracheal Obstruction Secondary to Cervical Liposarcoma Metastasis - Haoyu Chen; Song Zhang; Haining Zhou (Thoracic Cancer)
ABSTRACT Tracheal obstruction can arise from multiple conditions, including chronic obstructive pulmonary disease, asthma, foreign bodies, tumors, and acute heart failure. We report a case of a 43‐year‐old man with cervical liposarcoma who, following surgical excision, chemotherapy, and radiation, presented with severe dyspnea and was admitted to our hospital. A CT scan detected an endotracheal mass causing significant obstruction, suspected to be malignant. The patient required intensive care due to respiratory distress. Bronchoscopy revealed a red polypoid lesion causing nearly 90% tracheal narrowing, which was successfully resected using high‐frequency electrotrap and argon coagulation, confirming it as a metastasis from the previously treated liposarcoma. Remarkably, there were no significant recurrences after 6 months. While lung metastases are frequent, intratracheal metastasis is rare; this case is the first documenting bronchial and tracheal metastasis of liposarcoma. It highlights the dangers of airway obstruction and the need for timely intervention. Although CT scans are helpful in identifying intrabronchial tumors, bronchoscopy remains the gold standard for diagnosis and treatment, with several options available for urgent cases.